New or rare Madagascar tiger beetles—19. Description of Pogonostoma (Pogonostoma) natsuae sp. nov. and elaborated redescription of P. (M.) meridionale Fleutiaux (Coleoptera: Cicindelidae) - Moravec, Jiří; Razanajaonarivalona, Elisé Hugo; Hori, Michio (Zootaxa, 2020)
Pogonostoma (Pogonostoma) natsuae sp. nov. from southwestern Madagascar is described as new to science. The new species is compared to similar Pogonostoma (Pogonostoma) meridionale Fleutiaux, 1899, which occurs in the southernmost areas of Madagascar and whose elaborated redescription is presented. Both species are illustrated in colour photographs of their habitus and diagnostic characters of the type and other specimens.